1990
DOI: 10.1007/bf01650886
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin und Osteoporose — Kritische Durchsicht der Literatur 1980–1989

Abstract: Due to increasing old age and a prolonged life expectancy osteoporoses mainly of the involutional type have become very common and are thus of prime socio-medical importance. Recently considerable attention has been given to calcitonin as an aetiologic, prophylactic and therapeutic agent in osteoporosis. Since the subject is very controversial, the present study aims at critically evaluating the pertinent literature from 1980-1989: 1. A decreased stimulability of the thyroid C-cells and thus a diminished calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
3

Year Published

1992
1992
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
0
3
Order By: Relevance
“…Our results are in contrast to several therapeutic studies showing positive effects of pharmacological doses of calcitonin given intermittently, either subcutaneously or intranasally, on bone mineral density (Gruber et al 1984;Ringe & Wenzel, 1987;Haas et al 1990). The percentage of postmeno¬ pausal women was not higher in the group of patients with elevated calcitonin levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in contrast to several therapeutic studies showing positive effects of pharmacological doses of calcitonin given intermittently, either subcutaneously or intranasally, on bone mineral density (Gruber et al 1984;Ringe & Wenzel, 1987;Haas et al 1990). The percentage of postmeno¬ pausal women was not higher in the group of patients with elevated calcitonin levels.…”
Section: Discussioncontrasting
confidence: 99%
“…IMO was prevented by treatment with 1,25-dihydroxyvitamin Dy [8], a substance known to be able to stimulate bone resorption. The present results are in contrast to pre vious studies, having shown positive effects of CT on bone mass, also in low turnover states of bone metabolism [ 13]. However, in that study.…”
Section: Discussioncontrasting
confidence: 56%
“…This is in contrast to results showing diminished CT secretion in postmenopausal osteoporosis [13]. Inhibition of osteoblasts has been shown to occur in IMO already at day 3 after induction of IMO [3,4], and there is increased urinary calcium excretion [5].…”
Section: Discussioncontrasting
confidence: 53%